The influence of personality trait and demographics on financial decision making among Generation Y - Nga, Joyce Koe Hwee *; Leong, Ken Yien * (Emerald, 2013)
Purpose – Financial planning is important in promoting the social well-being of a nation. Without proper financial planning, individuals may be ill-prepared in coping with the escalating cost of living, medical costs as well as enjoying their desired quality of life. However, financial decision making is not always made in a rational manner. This study aims to investigate the influence of personality traits, genders and course majors on decision making dimensions of risk aversion, cognitive biases and socially responsible investing (SRI) criteria among Generation Y undergraduates. Design/methodology/approach – The study utilizes a sample of undergraduates from a business school in Klang Valley, Malaysia. The study adapts the Big 5 personality scales from McCrae and Costa. The scales for the financial decision making dimensions, namely risk aversion, cognitive biases and SRI constructs, were developed for this study based on concepts developed from the extant literature. The validity and reliability of the scales were tested using exploratory factor analysis and Cronbach’s alpha respectively. Hypotheses were tested using multiple linear regressions, t-tests and ANOVA methods. Findings – Conscientiousness, openness and agreeableness were found to have a significant influence on risk aversion, cognitive biases and SRI respectively. Gender and course majors taken were not significant in financial decision making. Research limitations/implications – Future research should extend this to different cohorts of individuals including working adults and retirees. The mediating influences of personality and moderating influences of demographic factors such as education level, age and religiousity should also be explored to better target potential investors and fulfill their financial goals. Practical implications – Awareness of the influence of specific personality traits in financial decision making would help financial planners tailor products more effectively to cater for the understanding and lifestyle of the younger generation. There may also be a need in the future for business schools to introduce courses on behavioural finance in their curriculum. Originality/value – Studies on financial planning have more often focused on rational aspects of financial decision making rather than on personality dimensions. This study bridges the gap by investigating the influence of the Big 5 personality traits in financial decision making. The study also posits that the influence of personality traits is more significant than demographic factors in financial decision making.